Cooperation Between Teachers and Parents of Foreign Students - Trzcińska-Król, Maria (International Journal about Parents in Education, 2023)
Recent years have contributed to the creation of many publications about the important role of parents in the education process and their cooperation with the school for fuller and more comprehensive development of the child. The role of parents, although not explicit, is increasingly appreciated by teachers and pedagogues in the process of adapting and building a satisfactory educational path for children and adolescents. Today, however, as a result of migratory movements of the population, the school is facing a new challenge: work in a culturally diverse environment. One of the issue is including foreign students and their parents in the school community. In the face of the constantly increasing number of foreign pupils in Polish schools, it is extremely important to know to what extent the Polish education system supports the dialogue and partnership between teachers and parents of foreign children. The essence of this paper is the presentation of the results of pilot studies conducted by the author in the Warsaw school environment. The aim of the research is to get to know the scope of cooperation and communication between teachers and parents of foreign students in Warsaw schools. The research was based on a cooperation model by Joyce L. Epstein (2010, 2019), referring to: parenting, communication, volunteering, learning at home, decision making and collaboration with the community. The presented research has the character of a diagnostic survey and it is an attempt to answer the following research questions: How does communication with parents of foreign students work? How teachers assess the parents’ attitude in terms of: parenting, volunteering, learning at home, decision making, collaborating with the community?